2011
DOI: 10.1007/s00484-011-0491-9
|View full text |Cite
|
Sign up to set email alerts
|

Weather, season, and daily stroke admissions in Hong Kong

Abstract: Previous studies examining daily temperature and stroke incidence have given conflicting results. We undertook this retrospective study of all stroke admissions in those aged 35 years old and above to Hong Kong public hospitals from 1999 through 2006 in order to better understand the effects of meteorological conditions on stroke risk in a subtropical setting. We used Poisson Generalized Additive Models with daily hemorrhagic (HS) and ischemic stroke (IS) counts separately as outcomes, and daily mean temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
52
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(62 citation statements)
references
References 27 publications
7
52
1
2
Order By: Relevance
“…40 In our analysis, similar effects of temperature were observed before and after Table 2 Pooled relative risks and their 95% posterior intervals of cold and hot temperatures on stroke mortality over multiple lag days in 8 adjusting for PM 10 , SO 2 , and NO 2 (data not shown), suggesting that our findings were robust against this potential confounder. We were unable to adjust for fine particles and ozone because they were not criteria pollutants in China and were not routinely monitored during the study period.…”
Section: Figuresupporting
confidence: 71%
See 3 more Smart Citations
“…40 In our analysis, similar effects of temperature were observed before and after Table 2 Pooled relative risks and their 95% posterior intervals of cold and hot temperatures on stroke mortality over multiple lag days in 8 adjusting for PM 10 , SO 2 , and NO 2 (data not shown), suggesting that our findings were robust against this potential confounder. We were unable to adjust for fine particles and ozone because they were not criteria pollutants in China and were not routinely monitored during the study period.…”
Section: Figuresupporting
confidence: 71%
“…Similar findings on low temperature and higher stroke occurrence were also reported in South Korea, 23 northern Portugal, 24 and Hong Kong. 8 On the other hand, hot temperature was linked to higher stroke risk in studies in Scotland, 25 Mantua (Italy), 9 New York City, 26 California, 27 Brisbane (Australia), 28 and 4 cities in Korea. 29 In the present study, we found that the associations between temperature and stroke mortality were often nonlinear-both low and high temperatures were linked to more stroke deaths.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…More often, humidity is treated as a confounding variable that may be related to both the predictor and response variables (Barnett et al, 2010;Zhang et al, 2014). This approach is a part of the analysis strategy in numerous studies (Cao et al, 2009;Goggins et al, 2012;Guo et al, 2012;Lim et al, 2013;Liu et al, 2011;Vaneckova and Bambrick, 2013;Wang et al, 2009), although this list is certainly not exhaustive. Alternate approaches incorporate humidity in biometeorological indices (such as AT or Hx) or include it as an input variable in human heat 20 balance models.…”
Section: Humidity and All-cause Mortality And Morbiditymentioning
confidence: 99%